A Study about the Types of Characters in the Adam Project Movie - Pascarini, Elsa Oktaviana; Utami, Ni Made Verayanti (Austronesian: Journal of Language Science & Literature, 2025)
This study explores the diverse types of characters depicted in The Adam Project movie using the characterization frameworks proposed by Nurgiyantoro (2010) and Pope (2005). Employing a qualitative descriptive method, the research identifies and categorizes six main characters-Adam Reed, young Adam Reed, Laura Shane, Louis Reed, Ellie Reed, and Maya Sorian-based on their roles and character traits. The findings reveal that protagonist characters dominate the film, followed by various character types such as major, minor, simple, dynamic, round, static, and antagonist roles. Each character’s classification is supported by specific scenes and dialogue extracted from the film and its transcript. The study demonstrates how character types contribute significantly to narrative development and provides a framework for analyzing character roles in cinematic storytelling. This analysis is expected to enhance understanding of character construction in film studies and serve as a reference for future character-based literary research.